Pengaruh model pembelajaran Think Pair Share berbantuan media Canva terhadap kemampuan berpikir kritis siswa - mela rafika yuliandari; Aditya Eska Wardana; Sukma Wijayanto (Borobudur Educational Review, 2023)
This study aims to determine the effect of the think pair share learning model assisted by Canva media on the critical thinking skills of fourth grade students at SD Negeri 3 Plososari, Kendal Regency. The research method used in this study is an experiment with a pre-experimental design. While the type of research used in this research is one group pretest-posttest. The sample used in this study were 22 grade IV students at SD Negeri 3 Plososari, Kendal Regency. Data collection in this study used a questionnaire instrument in the form of pretest-posttest and observation sheets. The questionnaire instrument was given twice, where the pretest instrument was given to students before being given treatment and the posttest instrument was given after students were given treatment. The statistical test used in testing the hypothesis uses a paired sample t-test assisted by SPSS 25. The results obtained in this study indicate that the Think Pair Share model assisted by Canva media influences the critical thinking skills of fourth grade students at SD Negeri 3 Plososari, Kendal Regency. It is proved that the average pretest score is 63.5 < posttest 78.81. Furthermore, the paired sample t-test obtained a significance result (2 taied) 0.000 <0.05, so it can be concluded that the Think Pair Share model assisted by Canva media has a significant effect on students' critical thinking skills.